PERUBAHAN TATA RUANG RUMAH PENGRAJIN GERABAH KLIPOH BOROBUDUR - Suzanna Ratih Sari; Nindyo S; Wiendu N; Diananta p (TATALOKA, 2012)
Klipoh is located in the northern part of Borobudur Central Java province,  is a famous pottery village after Nggundi village. Based on data,almost 80% of the people are making pottery. This become unique because the pottery they made similar to manuscript that stipulated at one of the relief Borobudur Temple.It means that the pottery tradition is actually inheritance by the anchestor. As one of villages in Borobudur, Klipoh is still remain traditional eventhough there are many changes and effects forced local value to be changed. But if we take a look into detail, there are some traditional values are still remain and some were already changed. They changed and rearrangedtheir house from ordinary living  to become pottery production  house. There were many rooms and spaces changed functionally based on their pottery needs that caused crowded and made inconfinience of the room user. From this phenomena, therefore, it was needed to focus the study more on the space transformation of traditional houses as one of the significant changes that made trouble for the room users occurred in Klipoh. By using qualitative research, it is expected to look into detail the space transformation due to some aspects.